A Microelectrode Study of Interfacial Reactions at the Platinum-Alkaline Polymer Interface. Issue 6 (1st January 2015) - Yim, Sung-Dae; Chung, Hoon T.; Chlistunoff, Jerzy; Kim, Dae-Sik; Fujimoto, Cy; Yang, Tae-Hyun; Kim, Yu Seung
Abstract : Hydrogen oxidation (HOR) and oxygen reduction (ORR) reactions at the platinum/alkaline ionomer interface were investigated using two different alkaline polymer electrolytes, i.e., benzyl-trimethyl ammonium tethered poly(phenylene) (ATM-PP) and phenyl-pentamethyl guanidinium tethered perfluorinated polymer (M-Nafion-FA-TMG). Substantial inhibition of HOR was taking place at the platinum-ATM-PP interface due to the possible cationic group adsorption of ATM-PP, whereas the reaction was virtually unaffected at the platinum-M-Nafion-FA-TMG interface after high anodic potential preconditioning. Moreover, the apparent ORR activity of platinum coated with M-Nafion-FA-TMG was found higher than that in 0.1 M tetra methyl guanidinium solution. In addition, the oxygen permeability of M-Nafion-FA-TMG was found to be ∼2.5 times higher than that of ATM-PP. The above properties of the perfluorinated polymer make it a very promising ionomeric binder for the use in both anode and cathode of alkaline membrane fuel cells.